University men`s ice hockey: rates and risk of injuries over 6-years - Rishiraj, N.; Lloyd-Smith, R.; Lorenz, T.; Niven, B.; Michel, M. (The Journal of Sports Medicine and Physical Fitness, 2009)
Aim. The aim of this study was to determine the injury rates of a Men`s Varsity Ice Hockey team over six-years. Data on ice hockey injury rates and profile continue to increase in the hope of assisting with injury prevention. Methods. The University of British Columbia Men`s Varsity team has been followed prospectively over a six-year period. All student-athletes completed a preseason medical examinations and physiological assessments. The team physician evaluated each injury and the team therapist completed the injury report forms and the attendance records for each player. Results. A total of 46215 player exposures were recorded. The combined injury rate was 3.70 injuries/1000 player game and practice exposures. A statistically significantly higher risk of injury was observed during games and the greatest risk of injury was observed during the second period. Forwards sustained greater percentage of injuries compared to defensemen and goalies. Sprains and strains accounted for 40% of all injuries, followed by concussions (13%). Non-contact injuries were most common, while the anatomy sustaining the most injuries was the head/neck/face region. A high percentage of the recorded injuries required less than seven days to return to full activity. Conclusion. The risk of injury for university ice hockey players is greater during games and is dependant on playing position. Players are prone to sprains and strains, which may not involve any contact. Concussion and knee joint injury rates continue to cause concern.